2017
DOI: 10.1007/s00281-017-0654-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine responses in newborns

Abstract: Immunisation of the newborn represents a key global strategy in overcoming morbidity and mortality due to infection in early life. Potential limitations, however, include poor immunogenicity, safety concerns and the development of tolerogenicity or hypo-responsiveness to either the same antigen and/or concomitant antigens administered at birth or in the subsequent months. Furthermore, the neonatal immunological milieu is polarised towards Th2-type immunity with dampening of Th1-type responses and impaired humo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 145 publications
(203 reference statements)
0
103
0
2
Order By: Relevance
“…In the UK and Australia, which have an accelerated primary vaccination schedule at 2, 3, and 4 months, higher incidence and hospitalisation rate is observed in those under 3 months old compared with older infants 7. Mortality is high in this group,189 possibly due to an immature immune system and incomplete primary immunisation 10…”
Section: How Common Is It?mentioning
confidence: 85%
“…In the UK and Australia, which have an accelerated primary vaccination schedule at 2, 3, and 4 months, higher incidence and hospitalisation rate is observed in those under 3 months old compared with older infants 7. Mortality is high in this group,189 possibly due to an immature immune system and incomplete primary immunisation 10…”
Section: How Common Is It?mentioning
confidence: 85%
“…However, vaccines have been less effective at reducing infection-related deaths in newborns (Amenyogbe et al, 2015). Compromised vaccine-induced immunity in infants has been attributed to the potentially tolerogenic nature of the neonatal immune system (Yu et al, 2018), the reduced functionality of newborn immune cells (Lee and Lin, 2013;Yu et al, 2018), and dampened immunity from pre-existing maternal antibodies (Saso and Kampmann, 2017). Strategies have been proposed to drive more effective immunity in newborns, including designing vaccines and adjuvants tailored to neonates (Saso and Kampmann, 2017;Whittaker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We next investigated the patterns of individual T cell population abundances over time from birth through one year. Previous studies focusing on a limited number of T cell subsets have suggested a straightforward model in which the fetal T cell developmental program is first biased towards tolerance and hyporesponsiveness, but then acquires, following repeat immune priming postnatally, conventional memory T cells with polarized cytokine functions (19)(20)(21)(22). To more comprehensively characterize the T cell populations that follow a PMA-directed program, we examined populations that were selected as statistical predictors of PMA using elasticnet regression (see "Mistimed Immune and Microbial Development Predict Respiratory Morbidity").…”
Section: Premature Birth Transiently Alters T Cell Developmentmentioning
confidence: 99%